Common Factor the x
x³ - x³ - 42x = 0
x(x² - x - 42) = 0
The middle term inside the parenthesis is - x
The first tern x² = 1
Find the sum of the middle term
Multiply the first term 1 times the last term 42 equals 42 and factor
factors of 42
1 x 42
2 x 21
3 x 14
6 x 7. . .←. .use these factors
- 7 and + 6 satisft the sum of the middle term
insert - 7x and + 6x into the equation
x(x² - x - 42) = 0
x(x² - 7x + 6x - 42 ) = 0
Group factor inside the parenthesis
x(x² - 7x) + (6x - 42) = 0
x[x(x - 7) + 6(x - 7) = 0
x(x + 6)(x - 7) = 0
- - - - - - -
Roots
x = 0
- - - - - - - -
Roots
x + 6 = 0
x + 6 - 6 = 0 - 6
x = - 6
- - - - - - - -
Roots
x - 7 = 0
x - 7 + 7 = 0 + 7
x = 7
- - - - - - - -s-
2007-06-27 06:39:27
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
x^3-x^2-42x
Here is the principle
Take out as much as you can that is common to all elements - in this case 'x'
This leaves x(x^2-x-42)
To factor the part in brackets we need to be able to work out two brackets (x+a)(x+b) that when expanded come to x^2-x-42
If we expand (x+a)(x+b) we get (x^2+ (a+b)x + ab) so in effect we are looking for two numbers that when multiplied together make -42 (so one will be minus) and that when added together total -1 (or you could regard the difference in absolute values as being 1)
The answer is obvious (6 & -7) but in other cases you would write down the factors and see which pair met your requirments. Later on you will be taught an equation to solve a general equation of the form ax^2 + bx + c (called a quadratic equation)
So the answer is x(x+6)(x-7)
2007-06-27 06:00:26
·
answer #2
·
answered by welcome news 6
·
0⤊
0⤋
x (x^2 - x - 42)
x (x - 7) (x + 6)
2007-06-27 05:36:02
·
answer #3
·
answered by TychaBrahe 7
·
0⤊
1⤋
x^3-x^2-42x
=x(x^2-x-42)
=x(x+6)(x-7)
2007-06-27 05:51:15
·
answer #4
·
answered by ђermiona 6
·
1⤊
2⤋
x(x-7)(x+6)
2007-06-27 05:37:48
·
answer #5
·
answered by miggitymaggz 5
·
0⤊
1⤋
x(x^2-x-42)
x(x-7)(x+6)
2007-06-27 05:36:57
·
answer #6
·
answered by JJ 4
·
0⤊
1⤋
Wow why don't yu help me??
2016-05-17 12:31:26
·
answer #7
·
answered by ? 3
·
0⤊
0⤋
This is x(x-7)(x+6). Please put extra effort in your studies. Don't take these short cuts. Thanks.
2007-06-27 05:47:49
·
answer #8
·
answered by Falguni S 2
·
0⤊
1⤋